Pengelolaan Supervisi Klinis (Studi Kasus di SMKN 1 Karangayar) - Sukarno, Aris; Sarjono, Yetty (Jurnal VARIDIKA, 2015)
The research is qualitative research and aims at investigating the management of clinic supervision in SMK N 1 Karanganyar. The data used in the research are comments, opinion and activities related to clinic supervision. The data analysis used Milness model analysis. The finding of the research shows that the clinic supervision in SMK N 1 Karanganyar is conducted well. In conclusion, the supervision clinicin in SMK N 1 Karanganyar involve teacher of SMK N 1 Karanganyar actively and openly that teachers can accept the result of the supervision. The supervision clinic use 5W + 1 H analysis. Supervision in SMK N 1 Karanganyar can change the behavior and attitude of the teacher significantly.